2016
DOI: 10.3122/jabfm.2016.06.160128
|View full text |Cite
|
Sign up to set email alerts
|

Almond "Appetizer" Effect on Glucose Tolerance Test (GTT) Results

Abstract: Background:The extent to which glucose intolerance can be acutely improved with dietary modification is unclear. The purpose of this study was to test the effect of ingesting a low-calorie almond preload ("appetizer") 30 minutes before oral glucose tolerance testing in glucose-intolerant individuals without diabetes.Methods: Twenty adults with prediabetes or isolated 1-hour glucose >160 mg/dL underwent 2 fasting oral glucose tolerance tests (GTTs)-1 standard GTT and 1 GTT 30 minutes after eating a half ounce (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 19 publications
0
17
2
Order By: Relevance
“…In summary, given the results from the meta-analysis of 12 RCTs [ 20 ] and chronic studies [ 21 , 22 , 23 , 24 , 25 , 26 ] that were not included in the meta-analysis [ 20 ], nut consumption benefits glycemic control regardless of the type of nut but the effect is small and the amount of nuts required is large. Moreover, nut consumption reduces postprandial glycemia responses as shown in all nine studies [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Glycemic Controlmentioning
confidence: 78%
See 1 more Smart Citation
“…In summary, given the results from the meta-analysis of 12 RCTs [ 20 ] and chronic studies [ 21 , 22 , 23 , 24 , 25 , 26 ] that were not included in the meta-analysis [ 20 ], nut consumption benefits glycemic control regardless of the type of nut but the effect is small and the amount of nuts required is large. Moreover, nut consumption reduces postprandial glycemia responses as shown in all nine studies [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Glycemic Controlmentioning
confidence: 78%
“…Peanut consumption significantly reduced the 60-min postprandial glucose response to high-glycemic load meals in healthy subjects [ 29 , 30 ]. Five acute meal studies with a crossover design examined the effect of almond intake on postprandial glycemia and insulinemia [ 31 , 32 , 33 , 34 , 38 ]. Almonds (28 g) with a test meal (bagel, juice, and butter) significantly lowered postprandial glycemia in seven subjects with T2DM by 30% ( p = 0.04), but not in 13 healthy subjects without T2DM, with no differences in insulinemia and the incretin hormone, glucagon-like peptide-1 (GLP-1) [ 38 ].…”
Section: Glycemic Controlmentioning
confidence: 99%
“…Table 5 summarizes various acute clinical studies of nut consumption, most of which focus on almonds [ 69 , 70 , 71 , 72 , 73 ]. In a randomized crossover trial in healthy subjects, almond intake decreased postprandial glycaemia and insulinaemia [ 69 ].…”
Section: Human Clinical Trialsmentioning
confidence: 99%
“…In impaired glucose-tolerant subjects, it was observed that the consumption of almonds with a meal also decreased blood glucose in plasma [ 71 ]. In a recent crossover study performed in pre-diabetic subjects, a preload of almonds decreased postprandial glycaemia [ 73 ]. In healthy and diabetic individuals, Cohen et al also showed a 30% reduction in postprandial glycaemia after almond consumption compared with a starchy meal [ 72 ].…”
Section: Human Clinical Trialsmentioning
confidence: 99%
“…A fascinating study by Crouch et al 15 demonstrates that giving patients with prediabetes an almond "appetizer" before a glucose tolerance test has a significant effect on the glucose tolerance test results. The idea of "priming the pancreatic pump" could lead to some promising lifestyle interventions for patients with prediabetes, and maybe even diabetics.…”
mentioning
confidence: 99%